2019
DOI: 10.1177/2325967119881959
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Patient-Reported Outcomes After Arthroscopic Rotator Cuff Repair

Abstract: Background:Rotator cuff repair is one of the most common surgical procedures performed on the shoulder. Previous studies have indicated that pain and disability can vary significantly between patients with similarly appearing rotator cuff tears on diagnostic imaging. Prior literature has compared functional outcomes between operative and nonoperative treatments as well as variability in surgical techniques. However, few studies have examined postoperative outcomes based on patient factors such as sex.Purpose:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…However, in this study the obtained data could be influenced by two inconsistent LHBT surgical procedures—tenotomy/tenodesis, which may have an impact on final results [ 42 ]. The smokers also had more often night pain, which also could be biased by the male/female ratio, since there were no females in the smoking population [ 43 ]. This field needs further research because there is no simple link between pain sensation and smoking habits [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study the obtained data could be influenced by two inconsistent LHBT surgical procedures—tenotomy/tenodesis, which may have an impact on final results [ 42 ]. The smokers also had more often night pain, which also could be biased by the male/female ratio, since there were no females in the smoking population [ 43 ]. This field needs further research because there is no simple link between pain sensation and smoking habits [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing gender disparities in PROs can be especially useful for analyzing operative indications, counseling patients preoperatively, setting patients' expectations, tracking operative outcomes, and possibly determining reimbursement. 6,8 Since 1993, the National Institute of Health (NIH) Revitalization Act has mandated the inclusion of women and minorities in clinical research. Since then, numerous studies have demonstrated the effect of gender on both clinical outcomes and PROs for a variety of conditions and procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous studies have demonstrated the effect of gender on both clinical outcomes and PROs for a variety of conditions and procedures. In the orthopedic literature, studies have been conducted evaluating the effect of gender on PROs and other outcomes for various orthopedic surgeries, including total knee arthroplasty (TKA), 3,11,25,26,31,35,44 total hip arthroplasty (THA), 3,4,12,26,35 total shoulder arthroplasty (TSA), 15 rotator cuff repair, 8 and others. 2,16 Considerable variability exists in gender-based outcomes for different orthopedic procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal disorders and injuries that are characterized by sexual dimorphism are not routinely considered by orthopedic surgeons when making treatment decisions [ 25 ]. This is surprising as sex differences in patient-related outcomes and functionality after orthopedic surgery are well described in the literature [ 26 , 27 , 28 , 29 ]. This observation might partly be caused by sex-specific postoperative morbidity and mortality [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%